2021 IEEE Virtual Reality and 3D User Interfaces (VR) 2021
DOI: 10.1109/vr50410.2021.00065
|View full text |Cite
|
Sign up to set email alerts
|

VR based Power Wheelchair Simulator: Usability Evaluation through a Clinically Validated Task with Regular Users

Abstract: Power wheelchairs are one of the main solutions for people with reduced mobility to maintain or regain autonomy and a comfortable and fulfilling life. However, driving a power wheelchair in a safe way is a difficult task that often requires training methods based on real-life situations. Although these methods are widely used in occupational therapy, they are often too complex to implement and unsuitable for some people with major difficulties. In this context, we collaborated with clinicians to develop a Virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In this study, the total VRSQ scores were 19.91 (SD 16.45) in the normal group and 15.83 (SD 21.14) in the MCI group. These scores are not of concern based on prior studies, which reported mean values of 11.87-44.46 (40)(41)(42). Moreover, our test could be considered as well-tolerated, as none of the subjects dropped out of the test due to motion sickness.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, the total VRSQ scores were 19.91 (SD 16.45) in the normal group and 15.83 (SD 21.14) in the MCI group. These scores are not of concern based on prior studies, which reported mean values of 11.87-44.46 (40)(41)(42). Moreover, our test could be considered as well-tolerated, as none of the subjects dropped out of the test due to motion sickness.…”
Section: Discussionmentioning
confidence: 69%
“…Our 3D test environments include an indoor, maze-like obstacle course [18] conceived by our clinical partners and a full-scale model of a city square [17]. The two environments have been created with the Unity Real-Time Development Platform, and they can be displayed using different interfaces: a standard monitor, a head-mounted display (as in [5]), and a pair of 3D glasses in an immersive room (www.irisa.fr/ immersia), as shown in Figure 4.…”
Section: Wheeled Platformsmentioning
confidence: 99%
“…In VR, the patients experienced a high sense of presence, and the level of cybersickness remained very low in the three circuits. In particular, the collected data indicate that using the simulator during a training phase could drastically reduce damage to the environment (walls, doors, and furniture) and driving accidents [18].…”
Section: Training In Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this project is to allow a maximum number of users to use a PWC in safety in daily life. For this purpose, a VR-based PWC driving simulator aiming to contribute to driving training for patients has been developed [ 22 ]. The simulator provides combined visual feedback and vestibular feedback in order to limit motion sickness.…”
Section: Introductionmentioning
confidence: 99%